Observations on Important Onion (Allium cepa L.) Pest: Exosoma thoracicum (Redtenbacher, 1843) - Özgen, İnanç (Niyazi ÖZDEMİR, 2018)
Exocoma thoracicum (Redtenbacher, 1843) have caused damage in the onion fields of Malatya province of Turkey. In this study, information about the damage situation is given. In the following years;  detailed studies on It’s management and damage are required of this species.
Keywords: Engineering; Mühendislik